Azacitidine as maintenance therapy in pediatric de novo acute myeloid leukemia - Wu, Chunping; Cai, Chunxia; Li, Mei; Li, Nainong; Zheng, Yongzhi; Zheng, Hao (Frontiers in Immunology, 2025)
BackgroundRelapse remains a major challenge in pediatric acute myeloid leukemia (AML), particularly in patients ineligible for hematopoietic stem cell transplantation (HSCT). Hypomethylating agents like azacitidine are hypothesized to target residual disease, but their efficacy and safety as maintenance therapy in de novopediatric AML require validation.MethodsIn this retrospective cohort study, 78 pediatric patients with de novoAML in remission after the C-HUANAN-AML 15 protocol were assigned to either azacitidine maintenance (n=27; subcutaneous 75 mg/m²/day, days 1-14 per cycle for 6 cycles) or observation (n=51) groups. Measurable residual disease (MRD) was monitored longitudinally via multiparameter flow cytometry (<0.1% threshold) and PCR for fusion transcripts. Key outcomes included event-free survival (EFS), overall survival (OS), cumulative incidence of relapse (CIR), and safety.ResultsAt a median follow-up of 34.6 months, azacitidine maintenance showed comparable EFS (77.7% vs. 77.0%, p = 0.688), OS (89.7% vs. 85.0%, p=0.368) and CIR (22.3% vs. 21.0%, p=0.838) to observation in the overall cohort. Subgroup analysis suggested a non-significant trend toward improved EFS (85.1% vs. 69.3%, p=0.198) and OS (92.9% vs. 81.6%, p=0.304) in intermediate-risk patients. However, among the 17 patients with core-binding factor AML (CBF-AML) and baseline fusion transcripts ≥0.1%, azacitidine maintenance (n=9) showed significantly superior EFS and CIR compared to observation (n=8) (EFS: 100% vs. 62.5%, p=0.048; CIR: 0.0% vs. 40.0%, p = 0.042). Although 40.7% of patients experienced grade 2-4 myelosuppression, all completed the treatment without dose reductions.ConclusionAzacitidine maintenance therapy may sustain molecular remission in specific subgroups of pediatric AML, particularly CBF-AML patients with persistent MRD after induction who are ineligible for HSCT. However, the potential benefits must be weighed against the toxicity profile. The optimal dosing and scheduling require further investigation, and broader application warrants validation through larger, prospective, randomized controlled trials.